CATATAN BARU : SPESIES KELELAWAR SEBAGAI RESERVOIR Lyssavirus DI PROVINSI BALI, INDONESIA - Ayu Pradipta Pratiwi (Balai Besar Penelitian dan Pengembangan Vektor dan Reservoir Penyakit (B2P2VRP) Salatiga, 2019)
Bats are known as reservoirs of more than 60 zoonoses, one of which is Lyssavirus. Lyssavirus is a zoonotic disease with a case fatality rate of 100% and endemic in 72 countries, including Indonesia. This study aims to determine the confirmed species of bats as Lyssavirus reservoirs in Bali Province. Bats are collected in remote forest ecosystems and settlements, remote and non-forested settlements, and distant beaches and settlements, in Jembrana, Badung, and Karangasem Regencies. The individual number of bats caught were 378, consisting of 14 genera and 24 species. PCR examination results showed three samples confirmed positive Lyssavirus, these were species of Tylonycteris robustula species in Jembrana district, Aethalops alecto in Karangasem Regency, and Cynopterus brachyotis in Badung Regency.